Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(A=4x-\sqrt{8}-\frac{\sqrt{x^3+2x^2}}{\sqrt{x+2}}\)
\(=4x-\sqrt{8}-\frac{\sqrt{x^2\left(x+2\right)}}{\sqrt{x+2}}=4x-\sqrt{8}-x=3x-\sqrt{8}\)
b) \(x=\sqrt{-2}\) (không thỏa mãn)
a)
\(M=2+\sqrt{\left(2x\right)^2-2.2x.3+3^2}\)
\(\Rightarrow M=2+\sqrt{\left(2x-3\right)^2}\)
\(\Rightarrow M=2+2x-3\)
\(\Rightarrow M=2x-1\)
b)
(+) x=5/2
=> \(M=2.\frac{5}{2}-1=5-1=4\)
(+) x= - 1/5
=> \(M=2.\frac{\left(-1\right)}{5}-1=-\frac{2}{5}-1=-\frac{7}{5}\)
a) \(B=\sqrt{\frac{\left(x-2\right)^4}{\left(3-x\right)^2}}+\frac{x^2+1}{x-3}=\frac{\left(x-2\right)^2}{3-x}+\frac{x^2+1}{x-3}\\ =\frac{-\left(x-2\right)^2+x^2+1}{x-3}=\frac{-x^2+4x-4+x^2+1}{x-3}=\frac{4x-3}{x-3}\)
b) khi x=0,5 thì
\(B=\frac{4\cdot0,5-3}{0,5-3}=\frac{2}{5}\)
a/ Ta có: A=\(\left(\frac{x-\sqrt{x}}{\sqrt{x}-1}+1\right):\left(\frac{x+\sqrt{x}}{\sqrt{x}+1}\right)=\left(\frac{\sqrt{x}\left(\sqrt{x}-1\right)}{\sqrt{x}-1}+1\right):\left(\frac{\sqrt{x}\left(\sqrt{x}+1\right)}{\sqrt{x}+1}\right)\)
\(=\left(\sqrt{x}+1\right):\left(\sqrt{x}\right)=\frac{\sqrt{x}+1}{\sqrt{x}}\)
b/ Ta có :\(x=7+4\sqrt{3}=3+4\sqrt{3}+4=\left(\sqrt{3}+2\right)^2
\)
\(\Rightarrow\sqrt{x}=|\sqrt{3}+2|=\sqrt{3}+2\)
Thay x vào A ta có:
A\(=\frac{\sqrt{x}+1}{\sqrt{x}}=\frac{\sqrt{3}+2+1}{\sqrt{3}+2}=\frac{\sqrt{3}+3}{\sqrt{3}+2}=\frac{\left(\sqrt{3}+3\right)\left(2-\sqrt{3}\right)}{\left(2-\sqrt{3}\right)\left(2+\sqrt{3}\right)}=\frac{3-\sqrt{3}}{1}=3-\sqrt{3}\)